Patatin‐like phospholipase domain‐containing protein 3 is involved in hepatic fatty acid and triglyceride metabolism through X‐box binding protein 1 and modulation of endoplasmic reticulum stress in mice. Issue 6 (2nd February 2016) - Ochi, Tsunehiro; Munekage, Kensuke; Ono, Masafumi; Higuchi, Takuma; Tsuda, Masayuki; Hayashi, Yoshihiro; Okamoto, Nobuto; Toda, Katsumi; Sakamoto, Shuji; Oben, Jude A.; Saibara, Toshiji
Abstract : Aim: Non‐alcoholic steatohepatitis (NASH) is the major cause of chronic liver disease worldwide. Endoplasmic reticulum (ER) stress is considered to be an important pathological characteristic in NASH. A sequence variation (I148M) in the patatin‐like phospholipase domain‐containing protein 3/adiponutrin (PNPLA3) gene is known to be associated with the development of NASH. However, PNPLA3 deficiency has been considered to not be associated with fatty liver disease. To clarify, therefore, the role of PNPLA3 in liver, we established PNPLA3 knockout (KO) mice and investigated the phenotypes and involved factors under ER stress. Methods: ER stress was induced by i.p. injection with tunicamycin or with saline at 0 and 24 h in KO and C57BL/6 (wild‐type [WT]) mice. At 48 h after the starting of treatment, blood and liver samples were studied. Results: Hepatic steatosis and triglyceride content were remarkably increased in WT mice than in KO mice under ER stress. The hepatic palmitate/oleate ratio was significantly higher originally in KO mice than in WT mice. Moreover, the expression of stearoyl‐coenzyme A desaturase‐1 (SCD1) in KO mice under ER stress was decreased further than that in WT mice. Expression of ER stress markers X‐box binding protein 1 (XBP1) and ERdj4 was increased in WT mice but not in KO mice under ER stress. Conclusion: We first demonstrated the hepatic phenotype of PNPLA3 deficiency under ER stress. Our observations would indicate that PNPLA3 has an important role in hepatic fatty acid metabolism and triglyceride accumulation through XBP1 under ER stress.